Holter monitoring for the screening of cardiac disease in diabetes mellitus: The non-invasive Holter monitoring observation of new cardiac events in diabetics study. (November 2015) - Nakao, Yoko M; Ueshima, Kenji; Nohara, Ryuji; Mizunuma, Yoshimi; Segawa, Ikuo; Tanaka-Mizuno, Sachiko; Yasuno, Shinji; Nakao, Kazuwa; Hiramori, Katsuhiko; Kihara, Yasuki
We investigated the usefulness of Holter monitoring to detect cardiac disease and predict future cardiovascular risk in asymptomatic diabetic patients. This is a multi-centre, prospective study in 406 asymptomatic diabetic patients. They were categorized into three groups based on findings of Holter monitoring. A total of 377 met inclusion criteria and were classified as low ( n  = 172), moderate ( n  = 136) and high risk ( n  = 69). In total, 86 in moderate and 53 in high risk receive further evaluation. In total, 29 in moderate and 25 in high risk were diagnosed as cardiac disease and 12 required additional treatment, including coronary intervention. Over 1.8 years of mean follow-up, 11 (16.5 per 1000 person-years) experienced cardiovascular events. The cumulative incidence in moderate and high risk was higher than that in low risk ( p  = 0.029 and p  = 0.014, respectively). Our study suggests that Holter monitoring may be a useful screening tool to detect cardiac disease and predict future cardiovascular risk in asymptomatic diabetic patients.